The Association Between Demographic, Socio-Economic, Smoking Habits and Food Cravings in Adolescents - Venessa, Benedicta; Muhammad, Harry Freitag Luglio; Ekawati, Fitriana Murriya (Review of Primary Care Practice and Education, 2024)
Background: Food cravings are one of the factors that can increase the risk of being overweight in adolescents. Food cravings can be influenced by several factors, such as smoking habits and demographic and socio-economic conditions. Objective: Therefore, this study aims to see whether there is a relationship between demographic, socio-economic conditions, and smoking habits with the incidence of food cravings in adolescents. Methods: This study used a cross-sectional study and was conducted online in July-September 2021 involving 249 respondents from 2 senior high schools in Gunungkidul Regency. Data on demographic, socio-economic conditions, and smoking habits were collected using the Global Youth Tobacco Survey questionnaire, while data on food cravings were collected using the Food Cravings Questionnaire-Trait-reduced questionnaire. Results: From this study, it was found that the variables gender (p value: 0.000), age (p-value: 0.028), and smoking frequency (p-value: 0.045) were significantly related to the FCQ-Tr score. Conclusions: Demographic conditions (gender and age) and smoking habits (smoking frequency) are associated with the incidence of food cravings. However, further research is needed with a wider population to prove the results of this study.